MARKETING SYSTEM OF “GULA PASIR” SNAKE FRUIT IN BEBANDEM DISTRICT, KARANGASEM REGENCY - Dwi Dili Aprianna Putri; Ketut Budi Susrusa; Gede Mekse Korri Arisenna (Faculty of Animal and Agricultural Science, Diponegoro University, 2020)
Bebandem Sub-district as one of the biggest Gula Pasir snake fruit producing regions that has several marketing system channels and has different prices in each channel. This research was conducted to determine the channel of Gula Pasir snake fruit marketing system, market structure, market conduct, and to find out the efficiency of the sugar snake fruit marketing system.The data used are quantitative data and qualitative data. The analysis used is descriptive qualitative analysis. The respondents of this study were 53 people consisting of 32 Gula Pasir snake fruit farmers and 21 traders. The marketing institutions involved are village level collecting traders, inter regency / city / island collectors and retailer. All respondents were determined using the snowball sampling method. The results of the study contained six marketing systems. Market structure at the farm level leads to medium concentration oligopsony market structure. Market conduct that occurs in the Gula Pasir snake fruit marketing system is already good, referring to the payment system and cooperation between farmers and marketing institutions. The trade fair channel VI is the shortest and most efficient channel with farmer's share of 67% and the trading margin of Rp. 500,000 / Kw.Keywords: Marketing System, Market Structure, Market Conduct, Efficiency Marketing, Gula Pasir Snake Fruit